2022
DOI: 10.3389/fmicb.2022.953738
|View full text |Cite
|
Sign up to set email alerts
|

Few Amino Acid Mutations in H6 Influenza A Virus From South American Lineage Increase Viral Replication Efficiency in Poultry

Abstract: In chickens, infections due to influenza A virus (IAV) can be mild to severe and lethal. The study of IAV infections in poultry has been mostly limited to strains from the North American and Eurasian lineages, whereas limited information exists on similar studies with strains from the South American lineage (SAm). To better evaluate the risk of introduction of a prototypical SAm IAV strain into poultry, chickens were infected with a wild-type SAm origin strain (WT557/H6N2). The resulting virus progeny was seri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The South American lineage represents a unique evolutionary clade with little information about its adaptability ( 2 , 23 , 24 ). Rimondi et al ( 23 ) recently showed that 20 passages in 3-weeks old chickens produced 13 amino acid substitutions that conferred a South American H6N2 capacity to increase replication in chickens. Here, we found that five amino acid substitutions arose after only five passages in 3-days old chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The South American lineage represents a unique evolutionary clade with little information about its adaptability ( 2 , 23 , 24 ). Rimondi et al ( 23 ) recently showed that 20 passages in 3-weeks old chickens produced 13 amino acid substitutions that conferred a South American H6N2 capacity to increase replication in chickens. Here, we found that five amino acid substitutions arose after only five passages in 3-days old chickens.…”
Section: Discussionmentioning
confidence: 99%